All‐Solution‐Processed Pure Formamidinium‐Based Perovskite Light‐Emitting Diodes. Issue 39 (12th August 2018) - Wang, Juanhong; Song, Chen; He, Zhiwei; Mai, Chaohuang; Xie, Gancheng; Mu, Lan; Cun, Yangke; Li, Jiali; Wang, Jian; Peng, Junbiao; Cao, Yong
Abstract: All‐solution‐processed pure formamidinium‐based perovskite light‐emitting diodes (PeLEDs) with record performance are successfully realized. It is found that the FAPbBr3 device is hole dominant. To achieve charge carrier balance, on the anode side, PEDOT:PSS 8000 is employed as the hole injection layer, replacing PEDOT:PSS 4083 to suppress the hole current. On the cathode side, the solution‐processed ZnO nanoparticle (NP) is used as the electron injection layer in regular PeLEDs to improve the electron current. With the smallest ZnO NPs (2.9 nm) as electron injection layer (EIL), the solution‐processed PeLED exhibits a highest forward viewing power efficiency of 22.3 lm W −1, a peak current efficiency of 21.3 cd A −1, and an external quantum efficiency of 4.66%. The maximum brightness reaches a record 1.09 × 10 5 cd m −2 . A record lifetime T 50 of 436 s is achieved at the initial brightness of 10 000 cd m −2 . Not only do PEDOT:PSS 8000 HIL and ZnO NPs EIL modulate the injected charge carriers to reach charge balance, but also they prevent the exciton quenching at the interface between the charge injection layer and the light emission layer. The subbandgap turn‐on voltage is attributed to Auger‐assisted energy up‐conversion process. Abstract : All‐solution‐processed pure formamidinium‐based perovskite light‐emitting diodes achieve record performance by suppressing the hole current while increasing the electron current. The device exhibits a power efficiency of 22.3 lm W −1, a current efficiency of 21.3 cd A −1, an external quantum efficiency of 4.66%, a luminance of 1.09 × 105 cd m −2, and T50 of 436 s at L 0 = 10, 000 cd m −2 .